Pendeteksian Wajah Hasil Dari Manipulasi Ai Pada Citra Digital - Nawawi, Haikal Engga; Rahmadewi, Reni; Nurpulaela, Lela (Jurnal Ilmiah Wahana Pendidikan, 2024)
Technology's improvement year by year has been really quick such as AI (Artificial Intelligence), nowadays AI is used in everything in human activity. Image manipulation by AI is becoming more popular since netizens often use it as their content on social media. This image generated by AI has a problem which is that the result of the image is really similar to the real face, so therefore the problem needs to be solved by some solution such as segmentation method and edge detection method. This method will generate the result by euclidean distance as the parameter. The final result, the image from Ai will not have the same shape of highlight on the eyes but the real one will have the same shape.